2019
DOI: 10.2147/idr.s199993
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effects of sub-inhibitory concentrations of meropenem and tigecycline on the expression of genes regulating pili, efflux pumps and virulence factors involved in biofilm formation by<em> Acinetobacter baumannii</em></p>

Abstract: Background: Sub-minimal inhibitory concentrations of antibiotics have been indicated to affect the biofilm formation in pathogens of nosocomial infections. This study aimed to investigate the effects of meropenem and tigecycline at their sub-minimum inhibitory concentrations (MICs) on the biofilm formation capacity of Acinetobacter baumannii ( A. baumannii) , as well as the expression levels of genes involved in biofilm formation, quorum sensing, pili as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 44 publications
8
35
1
Order By: Relevance
“…On the other hand, the efflux pumps especially the resistance-nodulation-cell division (RND) family confer low-level multidrug resistance and have several roles during the process of biofilm formation in A. baumannii . Moreover, these pumps have extruded actively the autoinducers associated with quorum sensing, and harmful molecules such as antibiotics and metabolic intermediates 24. In this present study, there was a significant association between the overexpression of adeJ and the capacity of biofilm formation, so that all strong biofilm producers and 81.5% of intermediate producers showed the overexpression of the adeJ .…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…On the other hand, the efflux pumps especially the resistance-nodulation-cell division (RND) family confer low-level multidrug resistance and have several roles during the process of biofilm formation in A. baumannii . Moreover, these pumps have extruded actively the autoinducers associated with quorum sensing, and harmful molecules such as antibiotics and metabolic intermediates 24. In this present study, there was a significant association between the overexpression of adeJ and the capacity of biofilm formation, so that all strong biofilm producers and 81.5% of intermediate producers showed the overexpression of the adeJ .…”
Section: Discussionsupporting
confidence: 54%
“…The genomic DNA of these isolates were extracted using the boiling method, as previously described 17. The uniplex PCR assays were performed for the molecular identifications of the bap, pgaA, abaI, ompA and csuE genes and efflux pumps, including adeB, adeJ and adeG in a final volume of 25 μL 15,24. The sequences and sizes of the primers used in this study are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same results were observed in R3 clinical isolates in the presence of PMB [70]. Meropenem at the concentration of 64 μg/mL and 128 μg/mL increased AbOmpA expression by 1.81 and 1.63 folds, respectively [71].…”
Section: Regulation Of Abompa Expressionsupporting
confidence: 74%
“…35 , 38 It has been found that there is differential expression of genes controlling biofilm formation, including genes regulating pili, efflux pumps, and virulence factors when A. baumannii is exposed to sub-inhibitory concentrations of antimicrobials, specifically Meropenem and Tigecycline. 39 This promotion of biofilm formation due to sub-inhibitory concentrations of antimicrobials leads to an increase in minimum inhibitory concentrations (MIC) and the minimum biofilm eradication concentration of these antimicrobials. This was thought to be due the exopolysaccharide matrix or the overexpression of efflux pumps.…”
Section: Behaviour and Biofilm Formationmentioning
confidence: 99%